Early-age restrained shrinkage cracking of GFRP-RC bridge deck slabs: Effect of environmental conditions. (November 2015) - Ghatefar, Amir; El-Salakawy, Ehab; Bassuoni, M.T.
Abstract: Most of codes and guidelines for glass fiber reinforced polymers (GFRP) - Reinforced Concrete (RC) are based on modifying corresponding formulas, originally developed for steel bars, taking into account the differences in properties and behavior between FRP and steel. The main objective of this research is to investigate the effect of cyclic environments on early-age cracking of GFRP-RC bridge deck slabs experimentally. Two full-scale (measuring 2500-mm long × 765-mm wide × 180-mm thick) cast-in-place slabs reinforced with similar amounts of reinforcement ratio of 0.7% with GFRP and steel bars, respectively, were tested in adiabatic laboratory conditions as control specimens. In comparison, two other GFRP-RC deck slabs were tested under freezing–thawing and wetting–drying conditions. The test results are presented in terms of materials degradation, cracking pattern, crack width, and spacing, and strains in reinforcement and concrete. Test results indicate that the minimum reinforcement ratio (0.7%) recommended by the Canadian Highway Bridge Design Code 2006 (CHBDC 2006) for bridge deck slabs reinforced with GFRP bars satisfied the serviceability requirements after being subjected to the simulated cyclic exposures.